Pembangunan kerangka kerja strategik CRM-I: Kajian kes di Institusi Pengajian Tinggi Awam - Nor Hapiza, Mohd Ariffin, Dr; Abd Razak, Hamdan, Prof. Dr.; Khairuddin, Omar, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.